"Influencia del remojo de semillas en solución bioestimulante sobre la germinación y vigor de plántulas de papaya CV. nacional (Carica papaya L.)". - Cedeño Sánchez, Jhon Henrry (2015)
The cultivation of papaya (Carica papaya L.) in Ecuador is considered a non-traditional fruit in terms of exports, is produced in the provinces of Santo Domingo, Guayas, Esmeraldas, Manabí and Morona Santiago, where three varieties which usually are grown ; Hawaiian, La Tainung (FORMOSA) and the National variety. Production goes mainly to the Netherlands, UK, Belgium, Germany, Canada, Peru and Spain. Proliferates cultivation by seeds, since asexual propagation either layers or in vitro involves higher production costs. The seeds have low genetic potential because of cross-pollination that occurs naturally. Given these drawbacks, the study of the effect of soaking the seeds in a solution bioestimulante as pre-germination treatment was raised. The experiment was conducted in the Canton Valencia in the province of Los Rios, soaking five times (24, 48, 72, 96 and 120 hours) was studied in a solution where three doses of bioestimulante BASFOLIAR® (10, 20 was added and 30 ml / L-1) of water. Objectives was raised determine the time and dose to stimulate germination in less time. Among the results, it was found that papaya seeds subjected to soak 72, 96 and 120 hours did not germinate, as such data is not presented in these treatments, the experimental design was randomized complete block factorial arrangement 3 x 5 + 1, using 6 replicates with 50 seeds for each treatment. The variables recorded were: days to germination, germination percentage, germination percentage efficiency, plant height and stem diameter, slenderness vigor index and dry weight. Analysis of the results obtained it is concluded; the time of 24 hours soaking greater germination and an acceleration in the number of days to germination, plant vigor (height and stem diameter) and dry matter per plant, but not in time was observed over 72 hours soaking ungerminated because any toxic component within basfoliar biostimulating composition. Dose of 10 ml, greater efficiency is achieved, and gender germination best results on the characteristics of the plant